2018
DOI: 10.1021/acsami.8b01765
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Au@Metal–Organic Frameworks for Promoting Raman Detection Sensitivity of Methenamine

Abstract: Abuse of methenamine in foodstuff is harmful to the health of people. Routine methods recommended by the national standard are indirect assays with complicated pretreatment of samples or less sensitivity. In this work, core-shell Au nanoparticles@inositol hexaphosphate@MIL-101(Fe) nanoparticles, designated as Au@MIL-101, are successfully synthesized by layer-by-layer assembly. Metal-organic framework (MOF; MIL-101)-modified AuNPs could narrow the distance between neighboring Au@MIL-101, which increases the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 27 publications
1
47
0
1
Order By: Relevance
“…In contrast, Cai et al. have observed a much higher EF, about sixfold, for methenamine previously adsorbed onto an LbL assembled core–shell AuNP–iron complex, whereas Sun et al. have achieved a similar EF = 6 for 4‐mercapto‐pyridine adsorbed onto LbL assembled core–shell Fe 3 O 4 –SiO 2 –AuNP nanoparticles.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…In contrast, Cai et al. have observed a much higher EF, about sixfold, for methenamine previously adsorbed onto an LbL assembled core–shell AuNP–iron complex, whereas Sun et al. have achieved a similar EF = 6 for 4‐mercapto‐pyridine adsorbed onto LbL assembled core–shell Fe 3 O 4 –SiO 2 –AuNP nanoparticles.…”
Section: Resultsmentioning
confidence: 89%
“…Although we have found an enhancement factor (EF) between three and four orders of magnitude for rhodamine B deposited onto the photocatalytic deposited AgNP substrates, Aoki et al have found a similar EF ¼ 4 for methylene blue adsorbed onto LbL films of AgNP and phospholipids, [12] and Liu et al have found a maximum of threefold EF for urea adsorbed onto a 3D Ag nanorod LbL assembly. [13] In contrast, Cai et al have observed a much higher EF, about sixfold, for methenamine previously adsorbed onto an LbL assembled coreshell AuNP-iron complex, [14] whereas Sun et al have achieved a similar EF ¼ 6 for 4-mercapto-pyridine adsorbed onto LbL assembled core-shell Fe 3 O 4 -SiO 2 -AuNP nanoparticles. It is worth mentioning that our method is capable of synthesizing and immobilizing AgNP in a single step, using UV light instead of chemical reducing agents.…”
Section: Raman Characterization and Sers Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure the sensitivity of the electrochemical sensor, various functional nanomaterials are usually employed for signal amplification [13][14][15]. As one of the research hotspots in recent years, metal-organic frameworks (MOFs) have been used in many fields, such as catalysis [16], supercapacitors [17], adsorption and separation [18], and sensing [19][20][21]. Tang and coworkers have developed a series of MOF-based Immunosensors for fluorescent or colorimetric determination [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Among the chosen materials reported, metal-organic frameworks (MOFs) [16][17][18], a type of crystalline material constructed with metal ions or metal clusters and organic ligands, have attracted the most attention because of their porous structures, diversity of precursors, and convenient synthesis [19][20][21]. Several materials [22][23][24] and semiconductors [25][26][27] of different sizes and shapes have been coated with MOFs to form composite materials. In addition, some biological macromolecules, such as proteins [28][29][30], enzymes [31][32][33][34][35][36], and cells [37,38], have been coated with MOFs under mild conditions, which is critical for the maintenance of their biological activity.…”
Section: Introductionmentioning
confidence: 99%